Does social value matters in the consumption of fast food - Abdul Majid, Izaidin; Ngeng, Miang Hong; Wong, Lai Soon; Buang, Nor Aisyah (2010)
Most of us do eat fast food and some might be addicted to it but seldom are we conscious of the motivation behind such consumption choice. Our research objective is to identify the key influencing factors that drive such choice and gauge whether the difference in the set of influencing factors for KFC and McDonald’s patrons is of statistical significant. To address these issues, we conduct questionnaire-guided interviews to a quota sample of patrons at randomly chosen outlet of KFC and McDonald’s in Penang. About 150 respondents each from KFC and McDonald’s fast food outlets were invited for a short questionnaire-interview after their meals. Data were collected in the morning, afternoon, evening and night session. The analysis entails factor analysis and logistic regression in determining the salient social factors that influence consumption. Findings from study shown that consumers were driven by Social Groups such as family, co-workers and friends and the desire to project a sociable, westernized and successful image. Our aim is to understand consumption choice behaviour that could turn into advantages in the competition. Another contribution could be in modifying attitude toward fast food consumption, for example, control consumption of fast food of the younger population.